Simulation of Non-Shock Loading of Tantalum - Partom, Yehuda (European Journal of Applied Sciences, 2022)
We discuss and perform hydrocode simulations of gradual dynamic loading of tantalum. We show that using the generally accepted approach to viscoplastic response, it’s not possible to reproduce some features of the test results. But when we use our overstress approach, we’re able to reproduce those features, including the initial spike of the elastic precursor wave.